Fine‐needle aspiration biopsy of prostate synovial sarcoma: A case report and review of the literature. Issue 2 (24th October 2016) - Maleki, Sara; Cajigas, Antonio; Moss, Jason; Ramesh, K. H.; Khader, Samer
Abstract : We describe a case of synovial sarcoma originating from prostate gland. The diagnosis was confirmed by fluorescent in situ hybridization analysis (FISH) for SYT rearrangement on the cell block. Synovial sarcoma is a high grade soft tissue malignancy with exceedingly rare involvement of genitourinary tract. However this entity should be considered in the differential diagnosis when dealing with aspiration biopsies of particularly deep seated lesions with spindle cell or small round blue cell cytomorphology. Diagn. Cytopathol. 2017;45:168–172. © 2016 Wiley Periodicals, Inc.